Regulation of Melanocortin-4 Receptor Pharmacology by Two Isoforms of Melanocortin Receptor Accessory Protein 2 in Topmouth Culter (Culter alburnus) - Tao, Min; Ji, Ren-Lei; Huang, Lu; Fan, Si-Yu; Liu, Ting; Liu, Shao-Jun; Tao, Ya-Xiong (Frontiers in Endocrinology, 2020)
Melanocortin-4 receptor (MC4R) plays important roles in regulation of multiple physiological processes, and interaction of MC4R and melanocortin receptor accessory protein 2 (MRAP2) is suggested to play pivotal role in energy balance of vertebrates. Topmouth culter (Culter alburnus) is an economically important freshwater fish in China. Herein we cloned culter mc4r, mrap2a, and mrap2b. Culter mc4r consisted of a 981 bp open reading frame encoding a protein of 326 amino acids. qRT-PCR revealed that mc4r, mrap2a and mrap2b were expressed primarily in the central nervous system. In the periphery, mc4r and mrap2b were expressed more widely in the male, while mrap2a was expressed more widely in the female. Culter MC4R was capable of binding to four peptide agonists and increasing intracellular cAMP production dose dependently. CaMC4R showed high constitutive activities in both Gs-cAMP and ERK1/2 pathways, which could be differentially modulated by caMRAP2a and caMRAP2b. Culter MRAP2a significantly increased Bmax and decreased agonist-stimulated cAMP, while MRAP2b increased cell surface and total expression but did not affect Bmax and agonist-stimulated cAMP. These results will facilitate future investigation of the MC4R in regulating diverse physiological processes in topmouth culter.